Digital Marketing Communications That Affect Customer Response of Mushroom Farming Community Enterprises Nakhon Nayok Province - Sanont, Rujikarn (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
This research aimed to test the structural equation model of the relationship between digital marketing, brand value perception, and customer response to the products of mushroom farming community enterprises. This study employed a quantitative research approach. The population consisted of individuals who visited digital media and purchased red reishi mushroom tea products through the online channels of the mushroom farming community enterprises. The sample size was 394 respondents, selected using a convenience sampling method. The research instrument was a questionnaire, which achieved an alpha coefficient score of 0.83. Data were analyzed using descriptive statistics, including frequency distribution, percentage, mean, and standard deviation. The structural equation modeling technique was employed to test the research hypotheses. The results revealed that the model based on the research hypothesis was consistent with the empirical data. The digital marketing communication variable significantly influenced brand value perception and customer response, with influence values of 1.77 and 1.43, respectively. Additionally, the brand value perception variable had a negative influence on customer response, with an influence value of -0.32.